Una descripción de la maduración del caminado de los niños mediante parámetros del análisis multifractal - Muñoz Diosdado, Alejandro; Angulo Brown, Fernando; del Río Correa, José Luis (Revista Mexicana de Ingenieria Biomedica, 2004)
The stride interval time series in normal human gait is characterized by slightly multifractal fluctuations. In this work we discuss multifractal properties of the stride-interval time series of healthy children gait compared with healthy young subjects. The maximum, asymmetry and width of the multifractal spectrum have been used to measure gait time series complexity. The series of small children have wider multifractal spectra; these spectra narrow as the boy’s age increases until the widths are closer to the widths of the healthy young subjects. The results indicate that mature stride dynamics may not be completely developed even in healthy 7 yr-old children; it is in older children (11-14 yr old) that stride dynamics approach the values observed in healthy young adults. The analysis of the spectra asymmetry shows that the spectra of young adults are almost symmetrical, the spectra of small children are very asymmetrical, children younger than 7 years old have a right-skewed spectrum and it becomes almost symmetrical as the age increases. We discuss the possible clinical applications of the multifractal analysis of the gait time series